Management of Cushing’s disease when surgery is a tricky option – a case report - Lucija Vusić; Vedrana Verić; Matea Živko; Velimir Altabas (Liječnički vjesnik, 2023)
Cushing’s disease, a form of Cushing’s syndrome, is caused by excess ACTH production, a hormone that regulates cortisol production, by a benign tumor in the pituitary gland. As a result, cortisol levels are elevated, while ACTH levels are not suppressed due to autonomous secretion. The primary treatment option is surgery. Other therapeutic modalities include drug therapy, radiation, and bilateral adrenalectomy in selected cases.